Avaliação da conectividade florestal em paisagem urbana - Ribeiro, Marina Pannunzio (Universidade Federal de São Carlos, 2019)
Urbanization is a crescent anthropogenic process, and it is also considered one of the major threats to natural areas and biodiversity conservation. Thus, in order to mitigate its impacts, many strategies have been developed, such as the creation of Protected Areas (PAs). However, to guarantee the effectiveness of Protected Areas in promoting biodiversity conservation, it is necessary to ensure connectivity among them. Thus, this study had as main objective evaluating the PA connectivity in an urban landscape. For this, we mapped land use and land cover using Remote Sensing images, by supervised classification. Further, we calculated landscape metrics (shape, area and near) to evaluate forest remnants structure in the landscape. For analyzing the functional connectivity among PAs, we used endemic Atlantic Forest bird species capacity of dispersion, obtained from literature review and experts consulting. Thus, impedance values for birds landscape connectivity were attributed for each land use/land cover type. The characterization of the movement of the species-focus by different types of land use/land cover was performed by the least-cost modeling between PAs, when the UCs was considered as nodes (source areas). We evaluated the land use/land cover patter of the low-cost paths (LCP) considering a 100m-buffer. Finally, functional connectivity among forest remnants was evaluated using the Graph Theory. The results show that the study area is highly urbanized, with a high forest fragmentation level composed mainly by small forest patches with irregular shapes but connected among each other. Moreover, we identified 11 forest remnants composing an ecological network, with great importance to support landscape connectivity. Those forest patches offer habitat availability, likewise PAs connectivity within the landscape. Among those patches, the largest one is the National Forest of Ipanema, and it is also the main forest patch in this landscape that supports functional connectivity and biodiversity conservation. The other patches identified as of great connectivity importance are in private properties and mainly in the riparian area of the Pirajibú River. Only two municipal PAs, of five existing in the study area, are included in the ecological network, and therefore are functionally connected. The others PAs were not included in the network, according to the conditions imposed in this work. Control and restoration actions of riparian areas, incentives for native vegetation conservation in private properties, regulation of the land use and land cover in the buffer zone of the PAs, increasing the matrix permeability, the restoration of important fragments, in addition to landscape planning with the focus on combating urban spreading are indicated actions to potentialize the PAs connectivity in urbanized landscapes.
Assessment of forest connectivity in urban landscape
Keywords: Redes ecológicas; Unidades de Conservação; Floresta urbana; Conservação florestal; Teoria dos Grafos; Caminho das ligações-ótimas; Mata Atlântica; Estrutura da paisagem; Ecological networks; Protected areas; Urban forest; Forest conservation; Graph Theory; Least-cost modeling; Atlantic forest; Landscape structure; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL